THE USE OF OLIVIA RODRIGO’S SONGS ON THE SPOTIFY APPLICATION TO IMPROVE VOCABULARY MASTERY FOR NINTH-GRADE STUDENTS AT SMP N 1 ROWOSARI - Irma Oktaviana; Nur Hidaya; Festi Himatu K (STKIP Subang, 2023)
ABSTRACT This research motivated by problem about the students at SMP N 1 Rowosari still lack an understanding of English. For example, when students are asked to read English sentences, their pronunciation is still wrong, it is difficult to translate, and they do not understand English vocabulary because according to them there are too many and confusing. This research aimed to (1) To find out the implication of the use Olivia Rodrigo’s songs in improving the vocabulary learning skills of ninth-grade students at SMP N 1 Rowosari. (2) To describe the benefits obtained by ninth-grade students at SMP N 1 Rowosari regarding the use Olivia Rodrigo’s songs on the Spotify Application to improve vocabulary skills. In this research, the researcher used a qualitative method to find out the increase in students’ vocabulary mastery by using songs that are heard through the Spotify application. The object of the research is ninth-grade students of SMP N 1 Rowosari which each class consists of 32 students. Researchers took one class among five classes to be used as a sample. The class taken is class IX-A. The method of collect the data are the pre-test, post-test, and questionnaire. The results obtained show that the average pre-test score is 56.87 and the post-test average is 81.40. It means that there is any significances difference between the students who are taught by using songs on the Spotify application and those taught without songs on the Spotify application. So, it can be concluded that there is an increase in students' vocabulary mastery. Keywords: Vocabulary, Song, Spotify.